2016
DOI: 10.1111/bjdp.12155
|View full text |Cite
|
Sign up to set email alerts
|

Understanding ironic criticism and empathic praise: The role of emotive communication

Abstract: Ironic criticism and empathic praise are forms of social communication that influence the affective states of others in a negative or positive way. In a sample of 76 typically developing children and adolescents (mean age = 11 years; 4 months; SD: 2 years; 8 months), we studied how understanding of emotional expression (facial expression of emotion) and emotive communication (affective theory of mind) was related to the ability to understand negatively valenced ironic criticism and positively valenced empathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
(137 reference statements)
2
2
0
5
Order By: Relevance
“…Consequently, they may have struggled to appropriately anticipate the emotional responses to the ironic comment. This finding supports previous literature, which has shown impairments in representing the mental states of others in autism [Agostino, Im‐Bolter, Stefanatos, & Dennis, 2017; Baron‐Cohen, Tager‐Flusberg, & Cohen, 1994; Baron‐Cohen, 1997; Frith, 2003; Hamilton, 2009; Happé, 1994; Jolliffe & Baron‐Cohen, 1999; Kapogianni, 2016; Sabbagh, 1999], including intentions (for discussion, see Williams & Happé, 2010). Ideally, this causal relationship would be tested by correlating ToM scores with the reading measures during irony comprehension.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, they may have struggled to appropriately anticipate the emotional responses to the ironic comment. This finding supports previous literature, which has shown impairments in representing the mental states of others in autism [Agostino, Im‐Bolter, Stefanatos, & Dennis, 2017; Baron‐Cohen, Tager‐Flusberg, & Cohen, 1994; Baron‐Cohen, 1997; Frith, 2003; Hamilton, 2009; Happé, 1994; Jolliffe & Baron‐Cohen, 1999; Kapogianni, 2016; Sabbagh, 1999], including intentions (for discussion, see Williams & Happé, 2010). Ideally, this causal relationship would be tested by correlating ToM scores with the reading measures during irony comprehension.…”
Section: Discussionsupporting
confidence: 93%
“…use ToM) to appropriately anticipate the emotional responses to the ironic comment. This finding supports the previous literature, which has shown impairments in representing the mental state of others in autism (Agostino, Im-Bolter, Stefanatos, & Dennis, 2017;Baron-Cohen, Tager-Flusberg, & Cohen, 1994;Baron-Cohen, 1997;Frith, 2003;Hamilton, 2009;Happé, 1994;Jolliffe, & Baron-Cohen 1999;Kapogianni, 2016;Sabbagh, 1999), including intentions (for discussion, see Williams & Happé, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…The ability to infer other people’s emotions and feelings is designated affective ToM ( Shamay-Tsoory et al, 2009 , 2010 ). Despite the theoretical relationship between comprehension of irony and affective ToM, only one study reported a mediation effect of affective ToM on the relation between age and understanding ironic criticism in school-aged children ( Agostino et al, 2017 ). Although we found an association between affective ToM and irony understanding in patients with schizophrenia, the regression results suggested that affective ToM no longer predict irony performance when controlling the effect of EF.…”
Section: Discussionmentioning
confidence: 99%